Glomus tumor of the stomach - Batra R; Mehta Anurag; Rama Mohan P; Singh K (Wolters Kluwer Medknow Publications, 2009)
Gastric glomus tumors are rare neoplasms. We report here a case of gastric glomus tumor in a 25-year-old female who presented with exsanguinating gastrointestinal hemorrhage. Clinically and on gross examination, the tumor was suspected to be a gastrointestinal stromal tumor (GIST). Histopathological and immunohistochemical evaluation revealed it to be a glomus tumor.